1991
DOI: 10.1093/ptj/71.9.666a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultrasound and Trolamine Salicylate Phonophoresis on Delayed-Onset Muscle Soreness

Abstract: The purpose of this study was to determine the effects of ultrasound and phonophoresis using an anti-inflammatory-analgesic cream (trolamine salicylate) on delayed-onset muscle soreness (DOMS). Repeated eccentric contractions were used to induce DOMS in the elbow flexors of 40 college-aged women. Subjects were then assigned randomly to one of four groups: (1) group 1 (n = 10) received sham ultrasound using placebo cream, (2) group 2 (n = 10) received sham ultrasound using trolamine salicylate cream, (3) group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
2
3

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 19 publications
1
21
2
3
Order By: Relevance
“…[13][14][15][16] Previous studies have established the therapeutic effectiveness of various types of NSAIDs gel PH on both acute and chronic musculoskeletal pain and disorders. [17][18][19][20] Because of the established efficacy of this modality, there are several ongoing studies with some controversies from previous studies. An example of this is the study of Kozanoglu et al [18] which reported that ibuprofen PH was not superior to conventional TUS in patients with knee OA and that both were found to be therapeutically effective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[13][14][15][16] Previous studies have established the therapeutic effectiveness of various types of NSAIDs gel PH on both acute and chronic musculoskeletal pain and disorders. [17][18][19][20] Because of the established efficacy of this modality, there are several ongoing studies with some controversies from previous studies. An example of this is the study of Kozanoglu et al [18] which reported that ibuprofen PH was not superior to conventional TUS in patients with knee OA and that both were found to be therapeutically effective.…”
Section: Discussionmentioning
confidence: 99%
“…This result corroborates previous studies concerning the efficacy of PH and TUS in relieving pain, improving function and enhancing healing in musculoskeletal disorders. [16][17][18][19][20] The reduction in pain and improved functional activity level could be a result of the local thermal and mechanical effects of TUS and the analgesic gels on tissues surrounding the painful knee.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many studies on phonophoresis, continuous ultrasound was used to enhance the delivery of anti-inflammatory drugs (Ciccone et al, 1991;Kozanoglu et al, 2003). Ultrasound waves are associated with nonthermal and mechanical effects such as vibration, pressure, and cavitation of cells as the waves pass through the tissue (Nyborg, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Intermittent cryotherapy was applied directly over the subjects' affected areas with the same procedure described in the DMT group. At the expiration of cryotherapy application, the treated part was cleansed with a towel and continuous ultrasound at zero (0) intensity and frequency settings (no US transmission) was applied with 1.5g of placebo aquasonic gel (devoid of methyl salicylate 15% cream) as coupling medium (Ciccone et al, 1991;McElnay et al, 2004) for 8 minutes.…”
Section: Methodsmentioning
confidence: 99%